1999
DOI: 10.1111/j.1469-7793.1999.129aa.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of inactivation and restoration from inactivation of the L‐type calcium current in human myotubes

Abstract: 1. Inactivation and recovery kinetics of L_type calcium currents were measured in myotubes derived from satellite cells of human skeletal muscle using the whole cell patch clamp technique. 2. The time course of inactivation at potentials above the activation threshold was obtained from the decay of the current during 15 s depolarizing pulses. At subthreshold potentials, prepulses of different durations, followed by +20 mV test pulses, were used. The time course could be well described by single exponential fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
2
10
2
Order By: Relevance
“…This calculates to be 611 pA, using 88% of the average calcium flux presented in Table 1. The obtained value is in good agreement with previous measurements of calcium current amplitudes in primary myotubes [15,22,27], providing an independent confirmation of our method for estimating the calcium fluxes in myotubes.…”
Section: Repeated Application Alters the Calcium Fluxsupporting
confidence: 90%
See 1 more Smart Citation
“…This calculates to be 611 pA, using 88% of the average calcium flux presented in Table 1. The obtained value is in good agreement with previous measurements of calcium current amplitudes in primary myotubes [15,22,27], providing an independent confirmation of our method for estimating the calcium fluxes in myotubes.…”
Section: Repeated Application Alters the Calcium Fluxsupporting
confidence: 90%
“…The procedure for obtaining satellite cells and the culturing of myotubes from these cells were the same as described in our earlier reports [9,15]. In brief, muscles obtained from young mice, following an approved protocol of the Ethics Committee of the University of Debrecen, were dissociated at 37 jC using collagenase (0.75 mg/ml; Type II, Sigma, St. Louis, MO, USA) and trypsin (1 mg/ml; Difco, Detroit, MI, USA) in a calcium/magnesium free phosphate buffer.…”
Section: Tissue Culturementioning
confidence: 99%
“…Anesthetics, especially the ketamine used in the present study, have substantial effects on the excitability of the cerebellar cortex, including PCs (Sato et al 1993;Schonewille et al 2006;Servais and Cheron 2005). The up-regulated L-type Ca 2ϩ channels are also likely to contribute to the differences in the oscillation frequencies, given that the recovery and restoration time constants of these channels are highly dependent on the depolarization level (Harasztosi et al 1999). Therefore by altering Ca 2ϩ conductance, anesthetics could alter the frequency of the oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…A small shift in V h,0.5 was also observed for I Ca,T but only in normal co-cultured cells. Another group (Sipos et al 1997;Harasztosi et al 1999) has found more positive values but their data are only derived from normal human cell cultures with high calcium ion concentrations in the bath media (10 mM), which probably led to the well-known charge screening effect and the resulting shift of inactivation curves towards positive values. Thus the coculture conditions seem to induce a resulting general decrease in the voltage-dependent availability of calcium channels, except for DMD cells where this decrease was significantly stepped down.…”
Section: Calcium Current Properties: Comparison With Aneural Culturesmentioning
confidence: 99%
“…Since one of the functions of calcium channel molecules is to transfer calcium ions into the cells, this process could be one of the potential candidates for contributing to the calcium entry and accumulation in DMD cells. In vitro studies on aneurally cultured cells have shown the existence of at least two types of voltage-dependent calcium current (T and L); their characteristics have been extensively studied in normal (Rivet et al 1990(Rivet et al , 1992Garcia et al 1992;Sipos et al 1997;Morill et al 1998;Harasztosi et al 1999) and DMD muscle cells (Rivet et al 1990), but no obvious differences in the voltage dependence and kinetics of these calcium currents have been observed, as expected from cells in which the resting intracellular calcium concentration remained similar. Consequently, in order to address a possible involvement of such calcium channels in the detected intracellular calcium concentration elevation, investigations in co-cultured human muscle cells were essential despite the low availability of DMD biopsies.…”
mentioning
confidence: 99%